Speleonectes williamsi, a new species of Remipedia (Crustacea) from the Bahamas - Hartke, Tamara R.; Koenemann, Stefan; Yager, Jill (Zootaxa, 2011)
We describe a new species of the genus Speleonectes (Crustacea, Remipedia, Nectiopoda) from an anchialine cave on Grand Bahama Island in the northern Bahamas. Speleonectes williamsi n. sp. is morphologically highly similar to Speleonectes emersoni from the Dominican Republic. However, morphological differences between the two species were detected in dissected body parts, such as the setal patterns of the antennae and trunk limbs, the terminal claws of maxillae and maxillipeds, and the frontal filaments.